Rechts- und Wirtschaftsprobleme der Gebietsreform in Estland - Mäeltsemees, Sulev (Estonian Discussions on Economic Policy, 2009)
The purpose of this paper is to analyze administrative-territorial reforms in Estonia, the comparative analysis of the public administration reforms in the Baltic Sea region, to formulate principles and purposes of the administrative-territorial reform in Estonia. An administrative-territorial reform has been topical since in the Estonia regained its independence but there are virtually no results. In 1995, a law was passed granting the Government the right to take decisions on the country’s administrative-territorial division. Both the local authorities and the central government can initiate changes in the administrative-territorial division. A public opinion poll must be conducted before any decision on changes can be taken, although the Government is not bound by the results of the opinion poll. By the spring of 2009, there were 227 local governments in Estonia, including 194 rural municipalities and 33 cities. The administrative-territorial organisation of Estonia needs changing. The average population of Estonian rural municipalities is less than 2,500 people and, in spite of mergers, there are still inexpedient units where the centrally located settlement is separated from its hinterland in administrative terms. However, one must be objective when preparing and carrying out the administrativeterritorial reform. The often expressed opinion that decreasing the number of rural municipalities would result in retrenchment of resources in terms of the number of local officials and administrative costs is misleading